Construction of Social Education Theory from ’Ulwan’s Perspective to Respond to Social Problems in the Digital Era/Society 5.0: A Qualitative Content Analysis Study - HS, Midi (Jurnal Pendidikan Islam, 2024)
Purpose – This study formulates the construction of a social education theory from ’Ulwan’s perspective as a basis for responding to social problems of the digital era/Society 5.0 (device addiction, disinformation, erosion of empathy). Design/methods/approach – A document-based qualitative study within a post-positivist paradigm. Primary source: Tarbiyatu al-Aulād fī al-Islām (’Ulwan). Secondary sources were selected according to relevance, authority, traceability, and conceptual contribution. Mayring’s qualitative content analysis was used for unitizing, deductive–inductive categorization, constant comparison, and theoretical synthesis; rigor was maintained through triangulation, an audit trail, and peer debriefing. Findings – ’Ulwan’s four pillars—(1) the instillation of a noble soul (piety, brotherhood, īṡār, courage); (2) safeguarding others’ rights (parents, relatives, neighbors, teachers); (3) ethics of social life (greeting, speaking, joking); (4) social oversight—critique (amar ma’ruf nahi munkar) —are coherently mapped onto the digital context. The model operates through the chain: value internalization (hablumminallāh-hablumminannās) to self-discipline & digital literacy (mediator) to ethical online behavior; moderated by family parenting patterns, school/madrasah culture, and platform design. Four propositions ready for empirical testing are advanced along that pathway. Research implications – The implementation package includes active family mediation and a “digital adab contract”; Islamic Netiquette modules in schools/madrasahs; community anti-hoax programs grounded in ukhuwah; as well as platform nudges (greeting reminders, friction before mass forwarding, user-friendly reporting channels).